Analysis of peer relationships in Korean middle school ınquiry and noninquiry science experiment classes - Kim, Dongryeul (Journal of Turkish Science Education, 2024)
In this study, inquiry science experiment classes for 30 students and noninquiry science experiment classes for different 30 students in the chapter named “Animals and Energy” of the second year of Korean middle school were conducted by the same teacher and the same class (6th class), The peer relationship between classmates before and after class was compared and analyzed by using a social network analysis method. As a result of the study, it was found that the inquiry experiment class has higher tie density, average number of friends, and connection compared to the noninquiry experiment class. In other words, it could be evaluated that the inquiry experiment class has a positive effectiveness on the relationship of the companion rather than the noninquiry experiment class. In the results of analyzing the status of fellowship relations regarding the degree of being nominated by fellow students and the degree of perfect connection within the group, it was evaluated that the inquiry experiment class was more effectiveness in improving the ratings of members and forming a fully connected community compared to the noninquiry experiment class. In addition, from a point of view that the type of alienation pattern decreases a lot in inquiry experiment class compared to noninquiry experiment class, it could be evaluated that there is a high possibility tha everyone participates in inquiry activities without alienated students in an experiment class.
Keywords: Inquiry; noninquiry; relation; experiment; social network analysis